2018
DOI: 10.1074/jbc.ra117.000758
|View full text |Cite
|
Sign up to set email alerts
|

The endoplasmic reticulum–resident collagen chaperone Hsp47 interacts with and promotes the secretion of decorin, fibromodulin, and lumican

Abstract: The build-up of diversified and tissue-specific assemblies of extracellular matrix (ECM) proteins depends on secreted and cell surface-located molecular arrays that coordinate ECM proteins into discrete designs. The family of small leucine-rich proteins (SLRPs) associates with and dictates the structure of fibrillar collagens, which form the backbone of most ECM types. However, whether SLRPs form complexes with proteins other than collagens is unclear. Here, we demonstrate that heat shock protein 47 (Hsp47), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
1
18
1
Order By: Relevance
“…Nascent α chains by different genes are encoded first to compose the N-terminus. The next step of assembly into a three-helix structure begins with the C-terminus of the nascent α chains to form procollagen, which is accompanied by certain chaperone proteins including heat shock protein 47, prolyl-hydroxylase, and protein disulfide isomerase to ensure precise alignment [9]. Hydroxylation and glycosylation in the endoplasmic reticulum are two main modifications that occur after translation, and the hydroxylation modification is regulated by vitamin C and pyruvate metabolism [10,11].…”
Section: Physiological and Physicochemical Properties Of Collagenmentioning
confidence: 99%
“…Nascent α chains by different genes are encoded first to compose the N-terminus. The next step of assembly into a three-helix structure begins with the C-terminus of the nascent α chains to form procollagen, which is accompanied by certain chaperone proteins including heat shock protein 47, prolyl-hydroxylase, and protein disulfide isomerase to ensure precise alignment [9]. Hydroxylation and glycosylation in the endoplasmic reticulum are two main modifications that occur after translation, and the hydroxylation modification is regulated by vitamin C and pyruvate metabolism [10,11].…”
Section: Physiological and Physicochemical Properties Of Collagenmentioning
confidence: 99%
“…This gene encodes the heat inducible protein HSP47, which is a member of the serpine family of proteinase inhibitors. HSP47 is crucial during pro-collagen biosynthesis and plays and important role in the secretion of decorin, fibromodulin and lumican for the assembly of the extracellular matrix 82 . In primary grade IV gioblastoma multiforme (GBM) primary cells, an over-expression of HSP47 promoted the expression of extracellular matrix (ECM)-related genes such as COL4A2 and MMP9 83 .…”
Section: Serpinh1mentioning
confidence: 99%
“…The present results reveal that a 24-hour stimulation with the modulated signal induced significant overexpression of DCNcore, but not of mature decorin, which could be due to the fact that the stimulus was applied at an early stage, prior to formation of the mature protein. On the other hand, it has been reported that the Hsp47 protein residing in the endoplasmic reticulum binds decorin with an affinity comparable to that of the interaction between Hsp47 and type I collagen, and that the lack of Hsp47 inhibits both the secretion of collagen and that of the SLRPs lumican and decorin (Ishikawa et al 2018). This inkling that besides playing a role in collagen folding and secretion (Ishida et al 2006;Ishikawa et al 2016;Nagai et al 2000) Hsp47 can intervene in SLRP secretion, contributes to better understanding the coordinated molecular interactions that control the secretion and organization of the functional collagen matrix.…”
Section: Discussionmentioning
confidence: 99%